2002
DOI: 10.3727/000000002783992406
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Nine Novel Human Small GTPases Showing Variable Expressions in Liver Cancer Tissues

Abstract: Digestion and detoxification are the two most important functions of the liver, and liver cells always keep a high metabolism level and active vesicular traffic. The malfunction of the vesicular traffic system might be a cause of the abnormal biological behavior of cancerous liver cells. The Ras superfamily is known to regulate various steps of vesicular traffic in eukaryotic cells. It would be significant to determine the change of vesicular transport molecules such as the members of Ras superfamily in carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 26 publications
3
96
0
3
Order By: Relevance
“…Rab24 (part of the Ras superfamily) is involved in vesicle transport, and we found that it was elevated in dysplastic A/J ACF. The potential significance of this observation with respect to colorectal cancer is based in part on earlier reports demonstrating high levels of this protein in hepatocellular carcinomas, prompting speculation that Rab24 may represent a proto-oncogene (42). Protease inhibitors have been associated with attenuation of tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Rab24 (part of the Ras superfamily) is involved in vesicle transport, and we found that it was elevated in dysplastic A/J ACF. The potential significance of this observation with respect to colorectal cancer is based in part on earlier reports demonstrating high levels of this protein in hepatocellular carcinomas, prompting speculation that Rab24 may represent a proto-oncogene (42). Protease inhibitors have been associated with attenuation of tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…NO-mediated Ras activation has been shown to mediate signal transduction processes in cells including Raf 180 and Erk activation 181,182 leading to many different effects depending on the specific cells 180,[182][183][184][185] . It appears that Ras mutations do not normally occur in human hepatocellular carcinoma development 186 but it is quite clear that the Ras pathway is activated, however as evidenced by significantly enhanced Raf overexpression and enhanced activation 187,188 . The Raf kinase is an important target for anticancer therapeutics 172 …”
Section: Ras Pathway In Cancer Developmentmentioning
confidence: 99%
“…However, the incidence of breast cancer may also be associated with other unknown genes, and studies have suggested that the tumorigenesis and metastasis of certain cancer types is strongly associated with the loss of Rab gene function (10)(11)(12). The Rab family is the largest subfamily of the small GTP-binding protein Ras superfamily, which plays a regulatory role as a GTP-dependent molecular switch at different stages of vesicular transport (13).…”
Section: Discussionmentioning
confidence: 99%